Molecular identification and biofilm-forming ability of Elizabethkingia species. (January 2022) - Puah, Suat Moi; Fong, Sam Pei; Kee, Boon Pin; Puthucheary, S.D.; Chua, Kek Heng
Abstract: Recently, Elizabethkingia species have gained attention as a cause of life-threatening infections. The identification via phenotypic methods of three important species- Elizabethkingia meningoseptica, E. anophelis and E. miricola is difficult. Our objectives were to re-assess 30 archived Flavobacterium meningosepticum isolates using 16S rRNA gene sequencing, ERIC-PCR, and biofilm formation assay. Twenty-four isolates were re-identified as E. anophelis and 6 as E. miricola. All of them had the ability to form biofilm as shown in microtiter plate assay based on crystal violet staining. Overall, E. anophelis had a higher specific biofilm formation index compared to E. miricola. A total of 42% (10 out of 24) of E. anophelis were classified as strong, 29% (7 out of 24) as moderate and 29% (7 out of 24) as weak biofilm producers. E. miricola, 17% (1 out of 6) isolates were strong biofilm producers, 50% (3 out of 6) moderate and 33% (2 out of 6) were weak producers. E. anophelis from tracheal secretions were significantly associated with ( p  = 0.0361) strong biofilm formation. In summary, this study showed that the isolates originally identified as F. meningosepticum were re-classified using the 16S rRNA gene as one of two Elizabethkingia species. The ability of E. anophelis to form strong biofilm in endotracheal tubes indicates their probable role in the pathogenesis of Elizabethkingia infections. Highlights: Using 16S rRNA gene, 24 E. anophelis and 6 E. miricola were re-identified. All isolates had the ability to form biofilm. E. anophelis from tracheal secretions were associated with ( p  = 0.0361) strong biofilm formation.